Multivalent nanoparticle-based vaccines protect hamsters against SARS-CoV-2 after a single immunization - Chiba, Shiho; Frey, Steven J.; Halfmann, Peter J.; Kuroda, Makoto; Maemura, Tadashi; Yang, Jie E.; Wright, Elizabeth R.; Kawaoka, Yoshihiro; Kane, Ravi S. (Communications biology, 2021)
The COVID-19 pandemic continues to wreak havoc as worldwide SARS-CoV-2 infection, hospitalization, and death rates climb unabated. Effective vaccines remain the most promising approach to counter SARS-CoV-2. Yet, while promising results are emerging from COVID-19 vaccine trials, the need for multiple doses and the challenges associated with the widespread distribution and administration of vaccines remain concerns. Here, we engineered the coat protein of the MS2 bacteriophage and generated nanoparticles displaying multiple copies of the SARS-CoV-2 spike (S) protein. The use of these nanoparticles as vaccines generated high neutralizing antibody titers and protected Syrian hamsters from a challenge with SARS-CoV-2 after a single immunization with no infectious virus detected in the lungs. This nanoparticle-based vaccine platform thus provides protection after a single immunization and may be broadly applicable for protecting against SARS-CoV-2 and future pathogens with pandemic potential. Chiba et al. describe the use of MS2 bacteriophage coat proteins to develop nanocarriers that display the SARS-CoV-2 spike proteins multivalently for vaccine applications. The vaccine elicited high neutralizing antibody titers and protected Syrian hamsters from virus infection after a single immunization.